Bromodomain Protein Brd4 Associated with Acetylated Chromatin Is Important for Maintenance of Higher-order Chromatin Structure - Wang, Ranran (American Society for Biochemistry and Molecular Biology, 2012)
Chromatin structure organization is crucial for regulating many fundamental cellular processes. However, the molecular mechanism that regulates the assembly of higher-order chromatin structure remains poorly understood. In this study, we demonstrate that Brd4 (bromodomain-containing protein 4) protein participates in the maintenance of the higher-order chromatin structure. Brd4, a member of the BET family of proteins, has been shown to play important roles in cellular growth control, cell cycle progression, and cancer development. We apply in situ single cell chromatin imaging and micrococcal nuclease (MNase) assay to show that Brd4 depletion leads to a large scale chromatin unfolding. A dominant-negative inhibitor encoding the double bromodomains (BDI/II) of Brd4 can competitively dissociate endogenous Brd4 from chromatin to trigger severely fragmented chromatin morphology. Mechanistic studies using Brd4 truncation mutants reveal that the Brd4 C-terminal domain is crucial for maintaining normal chromatin structure. Using bimolecular fluorescence complementation technology, we demonstrate that Brd4 molecules interact intermolecularly on chromatin and that replacing Brd4 molecules by BDI/II causes abnormal nucleosome aggregation and chromatin fragmentation. These studies establish a novel structural role of Brd4 in supporting the higher chromatin architecture.